2020
DOI: 10.3389/fncel.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Discharges in Tissue Slices From Pediatric Epilepsy Surgery Patients: Critical Role of GABAB Receptors in the Generation of Ictal Activity

Abstract: In the present study, we characterized the effects of bath application of the proconvulsant drug 4-aminopyridine (4-AP) alone or in combination with GABA A and/or GABA B receptor antagonists, in cortical dysplasia (CD type I and CD type IIa/b), tuberous sclerosis complex (TSC), and non-CD cortical tissue samples from pediatric epilepsy surgery patients. Whole-cell patch clamp recordings in current and voltage clamp modes were obtained from cortical pyramidal neurons (CPNs), interneurons, and balloon/giant cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 65 publications
(94 reference statements)
0
20
1
Order By: Relevance
“…3H) and lower input resistance (MWU: p= 0.0323, MD= 50.17, 95%CI= 2.587 to 76.10) (Fig. 3I) indicating fAHP neurons are most likely not part of the LTS neuron subtype as these results contradict previous literature on regular LTS interneuron input resistance and voltage sag (Beierlein et al, 2003, Li et al, 2009, Tremblay et al, 2016, Levinson et al, 2020) 6,4749 . The decrease in voltage sag of fAHP neurons may indicate deficits in HCN1 channels which play a role in Ih current, a contributor to enhanced frequency-dependent gain and possibly decreased excitability (Brennan et al, 2016, Herrmann et al, 2015, Kalmbach et al, 2018, Moradi Chameh et al, 2021) 7,15,50,51 .…”
Section: Resultscontrasting
confidence: 61%
See 3 more Smart Citations
“…3H) and lower input resistance (MWU: p= 0.0323, MD= 50.17, 95%CI= 2.587 to 76.10) (Fig. 3I) indicating fAHP neurons are most likely not part of the LTS neuron subtype as these results contradict previous literature on regular LTS interneuron input resistance and voltage sag (Beierlein et al, 2003, Li et al, 2009, Tremblay et al, 2016, Levinson et al, 2020) 6,4749 . The decrease in voltage sag of fAHP neurons may indicate deficits in HCN1 channels which play a role in Ih current, a contributor to enhanced frequency-dependent gain and possibly decreased excitability (Brennan et al, 2016, Herrmann et al, 2015, Kalmbach et al, 2018, Moradi Chameh et al, 2021) 7,15,50,51 .…”
Section: Resultscontrasting
confidence: 61%
“…3Aiii). Interestingly, L2/3 cortical pyramidal neurons in rats have been shown to have the fAHP followed by a fast ADP similar to Figure 3Ai that can trigger bursting which is a common phenotype seen in human epileptic brain tissue from cortex and hippocampus samples (Avoli et al, 1987, Higgs et al, 2009, Chen et al, 2011, Levinson et al, 2020) 6,32,43,46 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Increased spontaneous GABAergic activity and pacemaker GABA synaptic activity has been shown in samples with pathological high-frequency oscillations (HFOs) obtained from patients with FCD (Cepeda et al, 2014(Cepeda et al, , 2019. It has been recently shown that epileptiform synchronization, mediated by 4-aminopyridine (4AP)-containing medium, leading to in vitro ictal activity in the human FCD tissues may be facilitated by the decreased ability of GABA B receptors to control GABA release from interneuron terminals (D'Antuono et al, 2004;Levinson et al, 2020). Thus, it may be possible that such an increase in spontaneous GABA A receptor activity could be due to the altered function of presynaptic GABA B receptors.…”
Section: Discussionmentioning
confidence: 99%